Thin Air, Thick Vessels: Historical and Current Perspectives on Hypoxic Pulmonary Hypertension - Young, Jason M.; Williams, David R.; Thompson, A. A. Roger (Frontiers in Medicine, 2019)
The association between pulmonary hypertension (PH) and hypoxia is well-established, with two key mechanistic processes, hypoxic pulmonary vasoconstriction and hypoxia-induced vascular remodelling, driving changes in pulmonary arterial pressure. In contrast to other forms of pulmonary hypertension, the vascular changes induced by hypoxia are reversible, both in humans returning to sea-level from high altitude and in animal models. This raises the intriguing possibility that molecular drivers of hypoxic processes could be targeted to modify pulmonary vascular remodelling in other contexts. In this review, we outline the history of research into PH and hypoxia, before discussing recent advances in our understanding of this relationship at the molecular level, focussing on the role of the oxygen-sensing transcription factors, hypoxia inducible factors (HIFs). Emerging links between HIF and vascular remodelling highlight the potential utility of inhibiting this pathway in pulmonary hypertension and raise possible risks of activating this pathway using HIF-stabilising medications.